Polymorphisms of the tumor necrosis factor-α gene promoter predict for outcome after thalidomide therapy in relapsed and refractory multiple myeloma - Neben, Kai; Mytilineos, Joannis; Möhler, Thomas; Preiss, Astrid; Krämer, Alwin; Ho, Anthony Dick; Opelz, Gerhard; Goldschmidt, Hartmut (Blood, 2002)
Thalidomide (Thal) is a drug with antiangiogenic, anti-inflammatory, and immunomodulatory properties that was found to inhibit the production of tumor necrosis factor-α (TNF-α) in vitro. We studied single nucleotide polymorphisms at positions −308 and −238 of the TNF-α gene promoter and measured the corresponding TNF-α cytokine levels in 81 patients (pts) with refractory and relapsed multiple myeloma (MM) who were treated with Thal. In myeloma pts carrying the TNF-238A allele (n = 8), we found a correlation with higher pretreatment TNF-α levels in peripheral blood (P = .047). After Thal administration, this TNF-238A group had a prolonged 12-month progression-free and overall survival of 86% and 100% versus 44% and 84% (P = .003 andP = .07) in pts with the TNF-238G allele, respectively. These findings suggest that regulatory polymorphisms of the TNF-α gene can affect TNF-α production and predict the outcome after Thal therapy, particularly in those MM pts who are genetically defined as “high producers” of TNF-α.
Gesehen am 10.12.2021